Uterine salvage management for atonic postpartum hemorrhage using “modified lynch suture” - El-Sokkary, M. (BMC Pregnancy Childbirth, 2016)
BACKGROUND: To assess the effectiveness of the new modified technique in order to control bleeding in women presenting with atonic, flabby uterus compared to the most commonly described technique of classic B-Lynch suture. METHOD: This study included 160 women of uncontrolled atonic postpartum hemorrhage delivered by cesarean section at Ain Shams University Maternity Hospital between January 2013 and October 2015. Participants were randomly assigned following simple randomization procedures (computerized random numbers) and divided into two groups. Group, I (80 patients) operated upon by the modified (new technique) stitch while group II (80 patients) operated upon by the classic technique. The ultimate goals were to stop blood loss after placement of the sutures and avoid life-saving hysterectomy thus preserving the life and fertility of the patient. RESULTS: The modified new technique was done in 80 patients with atonic postpartum hemorrhage and it was found to be superior to the classic technique with a success rate 95 % (4 cases needed hysterectomy as a lifesaving measure) compared to 85 % with the classic technique (in 12 cases, a life-saving hysterectomy was done). CONCLUSIONS: This technique can replace the classic B-lynch in flabby unresponsive atonic uteri as it has 8 shaped placement of the stitch which causes more firm compression on the uterus and simultaneous bilateral uterine artery ligation. This technique was proved valuable and successful in many patients who suffer from uncontrolled massive postpartum hemorrhage (PPH).